Investigation of the presence of equine herpesvirus-1 (EHV-1) in tissue samples of aborted foals by histopathological, immunohistochemical, and Real-Time PCR techniques - Deniz, Sezgin; Gülçubuk, Ahmet; Sönmez, Kıvılcım; Altan, Eda; Aytemiz Danyer, Işıl; Gürel, Aydın; Yılmaz, Hüseyin (Journal of the Hellenic Veterinary Medical Society, 2024)
Equine herpesvirus-1 (EHV-1) is a cause of pneumonia, encephalitis, and abortion in horses. Abortions occur alive or dead in the last trimester of pregnancy. The aim of this study is to investigate the incidence of EHV-1 infections in the tissue samples of aborted stillborn and live-born foals and the foals which died soon after birth and compare and correlate the conventional histopathologic diagnosis with IHC and Real-Time PCR. For this purpose, tissue samples (lung, liver, spleen, kidney, placenta, and brain) of 38 foals from Istanbul, Kocaeli, Bursa, and Eskişehir provinces of Turkey between August 2009 and March 2011 were examined Real-Time PCR revealed 52.6 % positivity (20/38), whereas 39.4 % (15/38) positivity was achieved with IHC, which indicated a correlation between these two diagnostic methods. In histopathological evaluation, the inclusion body was found in at least one of the tissue sections belonging to the lung, spleen, and mostly liver of 20 foals (52.6%). Tissue samples of the foals found to be positive by IHC and PCR revealed histopathologic findings compatible with the characteristics of the disease.